2013
DOI: 10.9734/ajea/2013/4089
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Economic Efficiencies in Poultry Production in Imo State, Nigeria

Abstract: This study was carried out to estimate the technical and economic efficiencies of poultry farmers in Imo State, Nigeria. The data was collected with semi-structured questionnaire from 140 randomly selected poultry farmers. A stochastic frontier production function was estimated by using the maximum likelihood estimation technique to obtain the technical and economic efficiencies of poultry farmers. The mean technical efficiency of poultry farmers was 75 percent, while their mean economic efficiency was 21 perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
4
13
0
Order By: Relevance
“…The results presented in Table 1 indicate that DOC and feed become the major driver of broiler farms production. The results of this study are consistent with several studies such as Akhter & Rashid (2008); Ohajianya et al (2013), and Ezeh et al (2012) where DOC and feed are an influential factor in production. The results also in line with the research conducted by Pakage et al (2014) that revealed the number of DOC was the most influential factor of production of broiler farms with closed house cage system.…”
Section: Discussionsupporting
confidence: 92%
“…The results presented in Table 1 indicate that DOC and feed become the major driver of broiler farms production. The results of this study are consistent with several studies such as Akhter & Rashid (2008); Ohajianya et al (2013), and Ezeh et al (2012) where DOC and feed are an influential factor in production. The results also in line with the research conducted by Pakage et al (2014) that revealed the number of DOC was the most influential factor of production of broiler farms with closed house cage system.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the nutritional value of poultry meat and egg, the production in the country is very insufficient, as reflected by the wide interval between supply and demand of the products (Ohajinya et al, 2013). Local demand for poultry products in Nigeria is about 1.5 million tonnes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its contribution to the Gross Domestic Product (GDP) and provision of employment opportunities, poultry production is a major source of protein in the country. Poultry farming is an important agribusiness enterprise that has a great potential for providing additional income to our farming community and educated unemployed persons of the rural areas through creating self employment opportunities (Ohajianya, Mgbada, Onu, Enyia, Henri-Ukoh, Ben-Chendo and Godson-Ibeji, 2013). Due to the high population growth in Africa and growing income, the demand for eggs and poultry meat has significantly increased in recent years across large parts of the continent (World Health Organization 2010).…”
Section: Introductionmentioning
confidence: 99%